Clinical presentation of cutaneous manifestations in complex regional pain syndrome (type 1). - Kandi, Basak; Kaya, Arzu; Turgut, Dilara; Ozgocmen, Salih; Cicek, Demet (My University, 2007)
OBJECTIVE: Complex regional pain syndrome type I (CRPS I) is a primary polymorphic condition of persistent pain and swelling that frequently occurs secondary to trauma associated with vasomotor disorders. The aim of this study was to evaluate the cutaneous findings in patients with CRPS I. METHODS: Eighteen patients with CRPS I were included in the study. Written informed consent was obtained from all participants. RESULTS: Of the 18 patients with CRPS I, 9 (50%) had hyperhidrosis, while hypohidrosis was present in 2 patients (11.1%). Eight patients (44.4%) had hypertrichosis, and 1 patient (5.6%) had hypotrichosis. Five of the patients (27.8%) had nail changes. CONCLUSIONS: These cutaneous changes are not rare in CRPS I and generate difficulties for the patient; therefore, they should be prevented during the early stages of CRPS I with use of an effective treatment.
Keywords: Adult; Complex Regional Pain Syndromes; Female; Humans; Male; Severity of Illness Index; Skin Diseases; adult; article; complex regional pain syndrome; evaluation; female; hospitalization; human; male; pathology; skin disease